ANALISIS DAMPAK PEMEKARAN DAERAH KABUPATEN/KOTA TERHADAP PEMBANGUNAN MANUSIA DI PROVINSI ACEH - Muhammad Nizar; Mohd. Nur Syechalad; Eddy Gunawan (Syiah Kuala University, 2018)
AbstractThe purpose of this research is to ascertain the differences of development growth between expansion and main districts, also to determine the factors that influence human development in the expansion and main districts in Aceh Province. This research used descriptive analysis and panel data regression. The descriptive analysis showed that in 10 regencies and cities, expansion is effective because the HDI growth is higher then the main districts. namely: Simeulue, Aceh Singkil, Bireuen, Aceh Barat Daya, Nagan Raya, Aceh Jaya, Bener Meriah, Pidie Jaya, Langsa and Lhokseumawe. Whereas in 3 regencies/cities, expansion is not effective namely, Gayo Lues, Aceh Tamiang and Subulussalam. The panel data regression results showed that significantly influence HDI in expansion and main districts are GDP per capita and proverty, whereas unemployment rate was not significant. GDP per capita showed positive influence, while proverty had negative influence to HDI. GDP per capita’s influence to HDI is greater, while proverty’s influence is greater in main districts.